Oil palm industry digitalization for sustainable plantation production in community economic development. Issue 3 (June 2021) - Stella; Ginting, B; Saidin, O K; Azwar, T K D
Abstract: In industry 4.0, the use of digitization in oil palm industry has encouraged economic development. It can help the industry on the marketing. The government must ensure of the application provider on the industry digitization in trading. This research discusses how does the government regulate the use of digitization in the palm oil industry to guarantee the sustainable plantation products. The method employed the normative juridical analysis. It discusses government regulations also have major benefits for the digitization industry, namely ensuring sustainable plantations, reducing operating costs, and creating efficiencies that lead to increased exports of domestic products. The government has issued the information of electronic transactions in the Law Number 11 of 2008 in conjunction with Law Number 19 of 2016. It can eliminate against the industry concerning destruction, forest fires, and infiltration of the local springs caused by oil palm plantations. The result shows about the main benefits of the digitization on the oil palm industry. The oil palm plantation of digitization shows the aspects of production, social, economy, and environment. It recommends the industry should uphold the liability of plantation workers in their harvests and marketing. Therefore, fair business competition of the oil palm industry can be obtained.